2021
DOI: 10.1152/ajpgi.00370.2020
|View full text |Cite
|
Sign up to set email alerts
|

Gab1 in livers with persistent hepatocyte apoptosis has an antiapoptotic effect and reduces chronic liver injury, fibrosis, and tumorigenesis

Abstract: Grb2-associated binder 1 (Gab1) is an adaptor protein that is important for intracellular signal transduction by receptor tyrosine kinases that are receptors for various growth factors and plays an important role in rapid liver regeneration after partial hepatectomy and during acute hepatitis. On the other hand, mild liver regeneration is induced in livers of individuals with chronic hepatitis, where hepatocyte apoptosis is persistent; however, the impact of Gab1 on such livers remains unclear. We examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…GAB1 promotes BRCA metastasis by interacting with the critical component PAR3 of the PAR complex and EMT of mammary gland tumors. In chronic liver injury, GAB1 plays an essential role in inhibiting apoptosis and reducing liver injury, fibrosis, and tumorigenesis ( Mizutani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…GAB1 promotes BRCA metastasis by interacting with the critical component PAR3 of the PAR complex and EMT of mammary gland tumors. In chronic liver injury, GAB1 plays an essential role in inhibiting apoptosis and reducing liver injury, fibrosis, and tumorigenesis ( Mizutani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor receptor, a major family of receptor tyrosine kinases, plays a key role in the progression and resolution of liver fibrosis by interacting with HSCs, hepatocytes and immune cells ( Seitz & Hellerbrand, 2021 ). In addition, knockdown of Gab1 , an important protein in the receptor tyrosine kinase pathway, significantly exacerbated liver fibrosis in animal models ( Mizutani et al, 2021 ). According to KEGG pathway analysis, phagosome was most highly enriched pathway, which was consistent with other studies that revealed that autophagy and LC3-associated phagocytosis were closely related to the pathogenesis of liver fibrosis ( Li et al, 2020 ; Wan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…GAB1 is involved in diverse biological processes such as cell proliferation, survival, invasion and migration, cell differentiation, angiogenesis, and inflammation [ 11 , 67 , 68 , 69 , 70 ]. All these functions of GAB1 appear to be fundamental to the processes underlying malignant transformation, including tumor angiogenesis and metastasis ( Figure 3 ).…”
Section: Role Of Gab1 In Cancermentioning
confidence: 99%

The Role of GAB1 in Cancer

Pérez-Baena,
Cordero-Pérez,
Pérez-Losada
et al. 2023
Cancers